The Effect of Root Face Height and Width of Hot-Gas Welding Plate Heater on Tensile Strength of HDPE Sheet - Mochammad Shohib Salam; Agus Setiawan (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
Hot-Gas Welding is a welding process that is widely used in plastic materials. In previous studies, there was a phenomenon that occurred, namely the early connection of the parent material before the welding process which affected the tensile strength of HDPE sheets. The purpose of this study was to determine the effect of variations in root face height and width of the anvil heating plate on tensile strength, and also to determine the interaction of the two variables. The welding process of Hot-Gas Welding, by varying two independent variables namely root face height 0 mm, 0.8 mm, 1.6 mm, 2.4 mm and the width of the anvil heating plate 10 mm, 15 mm, and 20 mm. The controlled variables include HDPE material 5 mm thick, HDPE filler 4 mm thick, hot gas temperature 250 ℃, single v bevel shape, anvil plate temperature 150 ℃ and v grove angle 60º. The results of this study indicate that the root face height and anvil plate width affect the tensile strength of hot-gas welding HDPE sheets. The maximum value of tensile strength is 27.09 Mpa or 85.32% of the tensile strength of the parent material. The maximum tensile strength value is obtained from the interaction of the root face height of 2.4 mm and the width of the heating plate of 15 mm. Distortion and linear misalignment weld defects at the highest tensile strength results were identified the least.